PERAN RESPON EMOSI MEMEDIASI PENGARUH ATRIBUT PRODUK TERHADAP BRAND SWITCHING - Mahajaya Utama, Komang Try; Sudiksa, Ida Bagus (E-Jurnal Manajemen, 2017)
The purpose of this study to explain the role of emotional response in mediating the relationship between product attributes with brand switching at a former Samsung branded smartphone users who have moved using a smartphone Asus brand. The research was conducted on consumers in Denpasar using a questionnaire taken immediately. The sample size of 100 respondents using purposive sampling method. Data analysis techniques used path and Sobel test. The results showed that the product attributes and emotional responses significant and positive impact on brand switching, as well as the emotional response was significantly mediates the relationship between the influence of product attributes on brand switching. The practical implications derived from this study are for the Samsung Company should be able to do some innovations on smartphones of their production, so that consumers would be interested in Samsung smartphones and increase the level of customer loyalty, as well as reducing the level of consumer brand switching.
Keywords: Keyword: product attributes, emotional response, brand switching